Transient - Maglonzo, Margaux Isabel Y. (Animo Repository, 2022)
Transient is a 15-20 minute dystopian fictional short film with the main genre being psychological thriller in a postmodern treatment. It follows the journey of a soul named Mich, a liberal lesbian woman who lived an undesirable lifestyle in the eyes of the religious. Upon Mich’s death, her soul reaches Transient, the stopover place before souls go to either Ginhawa or Dusa. Here, she meets two old-timer souls in Mark and Karina. They learn about each other’s lives but Mich’s stay slowly turns into litanies where the two impose dogmatic ideologies. Simultaneously, Transient is also transforming—from the highly-organized, orderly environment to a darker, and more awfully frightening place. Transient tackles and critiques religion at the fundamental core of its structure - the belief in an afterlife. Set in a reimagined version of the afterlife inspired by Christian concepts of heaven and hell, the film zeroes in on the tendency of religion to oppress identities. Different elements of religious indoctrination are incorporated in order to highlight the coercive nature of religions when rationalizing the requirements a believer must conform to in order to receive the subsequent benefits the organization has to offer. From personal accounts, related literature and anecdotal experience from peers, the researchers note that behavior is shaped by dominant narratives purported by religious institutions. They then create a fictional character who finds her soul at the center of yet another form of religious othering in a pre-afterlife way station, drawing a parallel to the systemic problems embedded in religious promises of paradise.